Decoding colorectal cancer lung metastasis: a global research odyssey - Zhang, Xu; Wang, Liping; Fu, Tong; Duan, Xuchu; Wang, Hao; Chen, Yuqing; Liu, Xiaoyu (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) remains a major global health burden, particularly when complicated by pulmonary metastasis (PM), which significantly worsens prognosis and reduces survival despite active treatment. The absence of standardized therapeutic strategies for CRC with PM has driven research into its underlying biological mechanisms, including epithelial-mesenchymal transition, immune evasion, and tumor microenvironment dynamics.MethodsA bibliometric analysis was conducted on 2,645 publications related to CRC with PM retrieved from the Web of Science Core Collection (1991–2025). Analytical tools such as CiteSpace and VOSviewer were employed to map the intellectual structure, collaboration networks, and research hotspots within this domain.ResultsThe analysis identified China and Japan as the most prolific countries in CRC–PM research, with Robert M. Hoffman (USA) and David L. Morris (Australia) as the most productive authors, and Joachim Pfannschmidt (Germany) as the most frequently cited. Annals of Surgery was recognized as the most influential journal. Four primary research themes were identified: (1) molecular mechanisms underlying CRC lung metastasis, (2) surgical intervention strategies, (3) systemic therapies and clinical trials, and (4) clinical management and outcome evaluation. These studies reflect a growing emphasis on multidisciplinary approaches and translational research.ConclusionThe field has witnessed notable progress in multimodal treatment strategies, encompassing advances in surgical techniques, chemotherapy regimens, and targeted therapies, all of which have contributed to improved patient assessment and survival outcomes. Future research should focus on optimizing integrated therapeutic approaches and refining clinical management protocols to further improve outcomes for patients with CRC and pulmonary metastases.